Selective inhibition by antiflamrnin-2 of thromboxane B2 release from isolated and perfused guinea-pig lung - Lidia Sautebin; Giuseppe Cirino; Massimo Di Rosa (Mediators of Inflammation)
Antiflammin-2 (AF2) is a nonapeptide corresponding to the amino acid residues 246–254 of lipocortin-1 showing anti-inflammatory activity both in vitro and in vivo. The effect of AF2 on the thromboxane B2 (TXB2) and histamine release from isolated and perfused guinea-pig lungs has been studied. AF-2 (10–100 nM) inhibited leukotriene C4- (LTC4) (3 ng) and antigen-induced (ovalbumin, 1 mg) TXB2 release in normal and sensitized lungs, respectively. In contrast AF-2 (100 nM) did not modify TXB2 release induced by histamine (5 μg) or bradykinin (5 μg) in normal lungs. Antigen-induced histamine release was not affected by 100 nM AF-2 infusion. When tested in chopped lung fragments AF-2 (0.1–25 μM) did not modify the release of histamine and TXB2 induced by antigen (ovalbumin, 10 μg ml−1) or calcium ionophore A 23187 (1 μM). Our results show that the inhibitory effect of AF-2 on TXB2 release is selective and depends on the stimulus applied. In this respect AF-2 mimics, at least in part, the actions of both glucocorticoids and lipocortin-1.